A questão Fradesca (1903) a partir de charges de Raul Pederneiras nas revistas O Malho e Tagarela - Loyola, Luís Felipe Souto (2021)
This research aims to analyze cartoons signed by Raul Pederneiras, published in the illustrated magazines O Malho and Tagarela, which portrayed the conflict between Benedictine monks, the press and the society in May 1903, in the city of Rio de Janeiro. This conflict was called pejoratively by the press as questão fradesca (free translation, ‘friars issues’). Through drawing and humor, we can understand the possibility of cartoons presenting themselves as sources capable of presenting us evidences in the daily life of Rio de Janeiro during this period, wich involved the benedictine monks, Society and the government. Authors such as Elias Thomé Saliba, Marcos A. da Silva and Isabel Lustosa, help us rescuing the humor and image of the beginning of the 20th century, as well as inserting ourselves in the discussions of History, based on authors such as Peter Burke, Sandra Pesavento and Roger Chartier This evidences are also capable of revealing layers that goes from representations, to problems that directly involved the State, Church and society. We also understand that such imagetic productions allow us to identify speeches and positions through aesthetic options, acting as realizing images mediating the imagination between those who produce and those who receive.